Financial Systems, Crisis, and Performance of Non-Financial Firms - Dr. Ghulam Mujtaba Chaudhary; Dr. Sabahat Akram; Adeel Arshad (Research Journal of Social Sciences and Economics Review, 2023)
This study examined the effect of financial crisis on performance of firms selected from divergent financial systems. For empirical analysis, a sample of 1440 non-financial firms was selected from 32 countries. Secondary data of firm level variables were collected from different reliable published sources. Panel regression model was applied for analysis of data and effect of crisis was examined by adding a dummy variable in the regression model. Relative effect of crisis across different categories was probed with the help of appropriate interaction terms. The study didn’t find any significant effect of crisis on financial performance of selected firms. Similarly, the differential effect across different categories also remain insignificant. On the basis of results, the study concluded that financial system structure is not much relevant in integrated modern global economies. The study recommended to strengthen the financial systems and develop an integration of all of its components for better and vibrant outcomes. The study further recommended to improve the internal systems and overall infrastructure for achieving sustainable growth and coping with the shocks effectively.